Development of rural herbal entrepreneurship in Malaysia - Paul, Kamal Chandra; Hamzah, Azimi; Abu Samah, Bahaman; Ismail, Ismi Arif; Alby, Jeffrey Lawrence D'Silva (Canadian Center of Science and Education, 2013)
The purpose of this research is to highlight the critical success and failure factors among rural Malay herbal entrepreneurs in Malaysia. As this was an exploratory research, a case study method was used as it gave an in-depth explanation on the issues regarding rural herbal entrepreneurship. This study was conducted in MAHA (Malaysia Agriculture, Horticulture & Agritourism), Serdang, Selangor with ten herbal entrepreneurs – five successful entrepreneurs and five unsuccessful entrepreneurs. The result suggested that customer service know-how of the business and the past experience of the entrepreneur are the major key factors of success. On the other hand, failure factors are explored and the most crucial ones are the lack of access to financial support from appropriate government organization, poor infrastructure as well as corruption. This paper has vast implications for the rural herbal entrepreneurs as it gives insight into the reasons and factors that brought about failures and successes.